2014
DOI: 10.4067/s0717-97072014000300012
|View full text |Cite
|
Sign up to set email alerts
|

Cr+6 REMOVAL BY INDIGENOUS BACTERIA IN CONJUNCTION WITH DIFFERENT BIOWASTE MATERIALS: AN ECOFRIENDLY APPROACH

Abstract: Two Cr+6 reducing bacterial strains previously isolated from tannery effluents were used in the present study and identified as Pseudomonas aeruginosa Rb-1 and Ochrobacterum intermedium (Rb-2) by 16S rRNA sequencing. Different biowaste materials (waste tea leaves, carrot juice pulp, dry leaves of eucalyptus and rice husk) were assessed for sorption / removal of Cr +6 from aqueous solution of K 2 Cr 2 O 4 . Feasibility of mono and mixed cultures of indigenous bacterial strains was evaluated for Cr +6 removal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…For agitation speed, Batool and Hasnain 51 indicated that the biosorption of Cr 6+ is highly affected by the speed of agitation where moderate speeds (100–120 rpm) facilitate proper contact between the biomass and the metal ions in the aqueous solution compared with static conditions. Furthermore, a decrease in metal removal efficiency at higher speeds (up to 500 mg/l) may be a consequence of the vortex phenomenon attributed to the reduction of the contact between biomass active sites and metal ions 52 .…”
Section: Resultsmentioning
confidence: 99%
“…For agitation speed, Batool and Hasnain 51 indicated that the biosorption of Cr 6+ is highly affected by the speed of agitation where moderate speeds (100–120 rpm) facilitate proper contact between the biomass and the metal ions in the aqueous solution compared with static conditions. Furthermore, a decrease in metal removal efficiency at higher speeds (up to 500 mg/l) may be a consequence of the vortex phenomenon attributed to the reduction of the contact between biomass active sites and metal ions 52 .…”
Section: Resultsmentioning
confidence: 99%